2010
DOI: 10.1542/peds.2010-0856
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic and Clinical Benefits of Noninvasive Ventilation in Infants With Pierre Robin Sequence

Abstract: NRS is able to improve breathing patterns and respiratory outcomes for infants with severe upper airway obstruction attributable to a PRS, which supports its use as a first-line treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 31 publications
0
39
0
4
Order By: Relevance
“…This exceptional case underlines the legal and ethical problems associated with long-term NPPV in selected patients. Infants with maxillofacial malformations, such as those with Pierre Robin sequence, represent an increasing group of young children who may benefit from NPPV as an alternative to the more invasive tracheostomy [7] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This exceptional case underlines the legal and ethical problems associated with long-term NPPV in selected patients. Infants with maxillofacial malformations, such as those with Pierre Robin sequence, represent an increasing group of young children who may benefit from NPPV as an alternative to the more invasive tracheostomy [7] (Fig. 5).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of infants may benefit from NPPV in the newborn period, such as infants with Pierre Robin syndrome [7,8]. However, the extended use of NPPV is limited by the paucity of well-adapted industrial masks for these young children.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic testing is highly recommended for these patients because the pathogenesis of this condition can be multifactorial and syndromic in nearly half of the occurrences of PRS 1,[4][5][6][7][8] . Breathing impairment is a major problem in patients with PRS [9][10][11] . The assessment of the impairment is based on clinical parameters (episode of desaturation, spontaneously and during feeding and sleep) and growth of facial structures during the first two years of life [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Breathing impairment is a major problem in patients with PRS [9][10][11] . The assessment of the impairment is based on clinical parameters (episode of desaturation, spontaneously and during feeding and sleep) and growth of facial structures during the first two years of life [9][10][11][12] . Many clinicians suggest treating mild cases with prone positioning using special "sniffing air" beds or other non-invasive respiratory support 13 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Recently, Leboulanger and others have demonstrated that noninvasive ventilation may also be considered as an effective treatment for improving breathing pattern and respiratory outcomes in patients with PRS. 5 Despite the fact that conventional airway management techniques are usually effective for airway control in most patients with PRS, facial abnormalities that accompany PRS may lead to difficulties in both mask ventilation and endotracheal intubation in a subset of these patients. 1 Previously, several techniques have been described for management of difficult airway in patients with PRS.…”
Section: Introductionmentioning
confidence: 99%